Coumarins from Casimiroa edulis and their retinoic acid receptor agonist activity - Manami Haba; Naohito Abe; Ken-ichi Nakashima; Yuki Sakurai; Satoshi Okubo; Takao Yamaura; Makoto Inoue; Masayoshi Oyama (Natural Product Research, 2026)

Monitoring the immune landscape against rabies in domestic dogs, Japan - Yuri Amemiya; Satoshi Inoue; Ken Maeda; Akira Nishizono; Yusuke Inoue; Naoto Ito; Hiroshi Nishiura (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Arterial spin labeling imaging of epileptic seizures with and without status epilepticus: A descriptive study - Tatsuya Sato; Masaya Katagiri; Tomoyuki Inoue; Satoshi Kubo; Kota Sato; Takahiro Himeno; Takahiro Itaya; Yuka Terasawa (Acta Neurologica Belgica, 2026)

Behavioral sequences during courtship and territorial defense of male Benthochromis horii in Lake Tanganyika - Ryoichi Inoue; Masaya Morita; Satoshi Awata; Shun Satoh (Hydrobiologia, 2025)

Prevalence, geographic distribution, and transmission pathway of Camponotus yamaokai virus - Erika Okada; Kazuma Chiyoda; Kanata Sakaya Inoue; Kazuhisa Yamasaki; Mamoru Takata; Toshiyuki Satoh; Satoshi Koyama (Archives of Virology, 2025)

Genomic features and pathogenicity of atypical diarrheagenic Escherichia coli from a large foodborne outbreak - Kenji Ohya; Shouhei Hirose; Kohei Nishikaku; Takahiro Ohnishi; Kenichi Lee; Sunao Iyoda; Akiko Kubomura; Yukihiro Akeda; Katsumi Mizukami; Tomikatsu Suzuki; Kenji Takinami; Yuhji Taquahashi; et al. (International Journal of Food Microbiology, 2025)

Sex Pheromone of the Azalea Mealybug: Absolute Configuration and Kairomonal Activity - Yuma Sugawara; Hiromitsu Inoue; Satoshi Toda; Jun Tabata (Journal of Chemical Ecology, 2024)

Ant utilization of tree trunks in relation to environmental factors in a temperate forest - Kanata Sakaya Inoue; Kohei Nakatsuji; Satoshi Koyama; Yuta Kobayashi; Tomohiro Yoshida (Acta Oecologica, 2024)

The past, present, and a future for native charr in Japan - Kurt D. Fausch; Kentaro Morita; Jun-ichi Tsuboi; Yoichiro Kanno; Shoichiro Yamamoto; Daisuke Kishi; Jason B. Dunham; Itsuro Koizumi; Koh Hasegawa; Mikio Inoue; Takuya Sato; Satoshi Kitano (Ichthyological Research, 2024)
Charrs ( Salvelinus ) reach their southernmost distribution in Japan, and are uniquely adapted to the short, steep streams of this island archipelago. Southern Asian Dolly Varden ( Salvelinus curilus ) occur only in Hokkaido Island, whereas white-spotted charr ( Salvelinus leucomaenis ) range to southern Honshu. Both species diverged from an ancestral lineage during the late Pliocene/early Pleistocene, when lowered sea levels created semi-enclosed water bodies in the seas of Japan and Okhotsk. Genetic analyses showed S. curilus represents the most ancient divergence from the Dolly Varden ( Salvelinus malma ) - Arctic charr ( Salvelinus alpinus ) group, and revealed five lineages of S. leucomaenis which align differently than traditional subspecies. Japanese charr display diverse and flexible life histories including anadromous fish with partial migration, and fluvial, adfluvial, and resident forms. In Hokkaido, Dolly Varden are distributed upstream and white-spotted charr downstream. They coexist in narrow sympatric zones through adaptive shifts by Dolly Varden in behavior and morphology that facilitate benthic foraging. Both species hybridize with native and nonnative salmonids, and are displaced from microhabitats and decline in abundance when rainbow trout ( Oncorhynchus mykiss ) and brown trout ( Salmo trutta ) invade. Japan streams contain over 95,000 erosion control dams which create short stream fragments (medians ~200 m). This has increased extirpation of charr populations via lower genetic diversity and stochastic and demographic factors. Tributaries provide complex rearing habitats, afford refuges from floods, and supply recruits that sustain populations in mainstem fragments and create metapopulations in connected riverscapes. Charr play central roles in linked stream-riparian food webs, and cause direct and indirect effects that cascade to streambed algae and riparian predators when linkages are disrupted by anthropogenic effects or altered by native parasites. Many charr populations are threatened by habitat fragmentation and introgression or invasion by nonnative forms, but efforts to conserve charr are growing. These include restoring connectivity among pure populations above barriers that prevent invasions, protecting tributary nurseries, and instituting angling regulations to protect headwater populations. Key steps include inventorying pure populations, identifying conservation units, selecting appropriate management based on connectivity and biotic interactions, and engaging stakeholders and youth to engender an ethic for conserving irreplaceable charr lineages.

Congenital malformations caused by Akabane virus in porcine fetuses in southern Japan - Daisuke Inoue; Akimi Hayashima; Fumiko Suzuta; Yasuhiko Motomura; Yuta Kawamoto; Fumihiko Yoshino; Kotaro Morita; Yoshio Hirai; Shigeru Iwamatsu; Satoshi Nakazato; Kumiko Kimura; Tohru Yanase (Veterinary Research Communications, 2024)

Factors influencing the development of canine fear of thunder - Kazuya Okamoto; Kanata Inoue; Junnosuke Kawai; Haruka Yamauchi; Shumpei Hisamoto; Koji Nishisue; Satoshi Koyama; Toshiyuki Satoh; Mikako Tsushima; Mami Irimajiri (Applied Animal Behaviour Science, 2024)

Heterologous expression and functional characterization of cysteamine dioxygenase from the deep-sea mussel Bathymodiolus septemdierum - Kotaro Yoda; Toshiyuki Takagi; Tomoko Koito; Masahiko Okai; Hiroko Makita; Satoshi Mitsunobu; Takao Yoshida; Koji Inoue (Fisheries Science, 2023)
In invertebrates inhabiting hydrothermal vent areas, hypotaurine, a precursor of taurine, is thought to mitigate the toxicity of hydrogen sulfide in vent fluids. Information about hypotaurine synthesis pathways in invertebrates is limited, although two pathways, the cysteamine [2-aminoethanethiol (AET)] pathway and the cysteine sulfinate (CSA) pathway are known in mammals. In this study, we cloned a cDNA encoding AET dioxygenase (ADO), the central enzyme of the AET pathway, from the vent mussel Bathymodiolus septemdierum . In the encoded protein ( Bs ADO), functionally important residues, including metal-binding histidines, are conserved. In maximum likelihood phylogenetic analysis, Bs ADO clustered with ADOs of other invertebrates. By reverse transcription PCR, BsADO mRNA was detected in all tissues examined at similar levels, suggesting that its function is distinct from that of the CSA pathway, predominantly expressed in the gill. Bs ADO with a His tag, expressed in Escherichia coli in the presence of Fe 2+ , converted AET to hypotaurine, but Bs ADO expressed in the absence of iron exhibited lower activity. Bs ADO was active from pH 8 to 11, and from 0 °C to 37 °C, with a peak at 20 °C. This is the first functional characterization of ADO in marine invertebrates.

Incorporative mixing in microreactors: Influence on reactions and importance of inlet designation - Shusaku Asano; Taisuke Maki; Shogo Inoue; Sumito Sogo; Masashi Furuta; Satoshi Watanabe; Yosuke Muranaka; Shinji Kudo; Jun-ichiro Hayashi; Kazuhiro Mae (Chemical Engineering Journal, 2023)

17β-neriifolin from unripe fruits of Cerbera manghas suppressed cell proliferation via the inhibition of HOXA9-dependent transcription and the induction of apoptosis in the human AML cell line THP-1 - Shohei Takase; Young Sook Yun; Fuki Moriya; Saaya Sekine; Satoshi Yotsumoto; Katsunori Miyake; Tadahiro Yahagi; Akihiro Ito; Hideshi Inoue (Journal of Natural Medicines, 2023)

Expression and localization of CD63 in the intracellular vesicles of odontoblasts - Miwako Matsuki-Fukushima; Kaoru Fujikawa; Satoshi Inoue; Masanori Nakamura (Histochemistry and Cell Biology, 2022)

Sleep Apnea Syndrome (SAS) Clinical Practice Guidelines 2020 - Tsuneto Akashiba; Yuichi Inoue; Naohisa Uchimura; Motoharu Ohi; Takatoshi Kasai; Fusae Kawana; Shigeru Sakurai; Misa Takegami; Ryo Tachikawa; Takeshi Tanigawa; Shintaro Chiba; Kazuo Chin; et al. (Sleep and Biological Rhythms, 2022)
The prevalence of sleep-disordered breathing (SDB) is reportedly very high. Among SDBs, the incidence of obstructive sleep apnea (OSA) is higher than previously believed, with patients having moderate-to-severe OSA accounting for approximately 20% of adult males and 10% of postmenopausal women not only in Western countries but also in Eastern countries, including Japan. Since 1998, when health insurance coverage became available, the number of patients using continuous positive airway pressure (CPAP) therapy for sleep apnea has increased sharply, with the number of patients about to exceed 500,000 in Japan. Although the “Guidelines for Diagnosis and Treatment of Sleep Apnea Syndrome (SAS) in Adults” was published in 2005, a new guideline was prepared to indicate the standard medical care based on the latest trends, as supervised by and in cooperation with the Japanese Respiratory Society and the “Survey and Research on Refractory Respiratory Diseases and Pulmonary Hypertension” Group, of Ministry of Health, Labor and Welfare and other related academic societies, including the Japanese Society of Sleep Research, in addition to referring to the previous guidelines. Since sleep apnea is an interdisciplinary field covering many areas, this guideline was prepared including 36 clinical questions (CQs). In the English version, therapies and managements for SAS, which were written from CQ16 to 36, were shown. The Japanese version was published in July 2020 and permitted as well as published as one of the Medical Information Network Distribution Service (Minds) clinical practice guidelines in Japan in July 2021.

A Rapid Method to Measure Serum Retinol Concentrations in Japanese Black Cattle Using Multidimensional Fluorescence - Yoshio Tamura; Hiroki Inoue; Satoshi Takemoto; Kazuo Hirano; Kazutoshi Miyaura (Journal of Fluorescence, 2021)
Vitamin A levels in fattening Japanese Black cattle affect meat quality; therefore, it is important to monitor serum retinol concentrations. To simplify and accelerate the evaluation of serum retinol concentrations in cattle, we developed a new predictive method using excitation-emission matrix (EEM) fluorescence spectrophotometry. For analytical comparison, the concentration of serum retinol was also measured using the conventional HPLC method. We examined excitation (Ex) and emission (Em) wavelengths of cattle serum, which were 250–450 and 250–600 nm, respectively. Parallel factor analysis separated four components from EEM data, one of which was related to retinol. Next, a partial least square regression model was created using the obtained EEMs as explanatory variables and accrual measurement values as objective variables. The determination coefficient value ( R 2 ), root mean squared error of prediction (RMSEP), and the ratio of performance to deviation (RPD) of the model were determined. A comparison with reference values found that R 2 , RMSEP, and RPD of the calibration model were 0.95, 6.4 IU/dl, and 4.2, respectively. This implies that EEM can estimate the serum retinol concentration with high accuracy. Additionally, the fluorescent peaks that contributed to the calibration, which were extracted from the regression coefficient and variable importance in projection plots, were Ex/Em = 320/390 and 330/520 nm. Thus, we assume that this method observes not only free retinol, but also retinol-binding protein. In conclusion, multidimensional fluorescence analysis can accurately and quickly determine serum retinol concentrations in fattening cattle.

Correction to: Herding mechanisms to maintain the cohesion of a harem group: two interaction phases during herding - Monamie Ringhofer; Clark Kendrick Go; Sota Inoue; Renata S. Mendonça; Satoshi Hirata; Takatomi Kubo; Kazushi Ikeda; Shinya Yamamoto (Journal of Ethology, 2021)
The article Herding mechanisms to maintain the cohesion of a harem group.

Effect of viral DNA methylation on expression of hepatitis B virus proteins depends on the virus genotype - Takuya Nakamura; Jun Inoue; Masashi Ninomiya; Eiji Kakazu; Tomoaki Iwata; Satoshi Takai; Akitoshi Sano; Takayuki Kogure; Tooru Shimosegawa; Atsushi Masamune (Virus Genes, 2020)

A series of commentaries for a symposium entitled “Session 3SDA - Optogenetics: applying photoreceptor for understanding biological phenomena” - Satoshi P. Tsunoda; Keiichi Inoue (Biophysical Reviews, 2020)

Feral horses’ (Equus ferus caballus) behavior toward dying and dead conspecifics - Renata S. Mendonça; Monamie Ringhofer; Pandora Pinto; Sota Inoue; Satoshi Hirata (Primates, 2020)

Herding mechanisms to maintain the cohesion of a harem group: two interaction phases during herding - Monamie Ringhofer; Clark Kendrick Go; Sota Inoue; Renata S. Mendonça; Satoshi Hirata; Takatomi Kubo; Kazushi Ikeda; Shinya Yamamoto (Journal of Ethology, 2020)
In animal groups, individual interactions achieve coordinated movements to maintain cohesion. In horse harem groups, herding is a behavior in which males chase females from behind; it is considered to assist with group cohesiveness. However, the mechanisms by which the individuals move to maintain group cohesion are unknown. We applied novel non-invasive methods of drone filming and video tracking to observe horse movements in the field with high temporal and spatial resolution. We tracked all group members and drew trajectories. We analyzed the movements of females and found two phases of interactions based on their timing of movement initiation. The females that moved first were those nearest to the herding male, while the movement initiation of the later females was determined by the distance from the nearest moving female, not by the distance from the herding male. These interactions are unique among animal group movements and might represent a herding mechanism responsible for maintaining group cohesion. This might be due to long-term stable relationships within a harem group and strong social bonds between females. This study showed that the combination of drone filming and video tracking is a useful method for analyzing the movements of animals simultaneously in high resolution.

Correction to: spatial positioning of individuals in a group of feral horses: a case study using drone technology - Sota Inoue; Shinya Yamamoto; Monamie Ringhofer; Renata S. Mendonça; Carlos Pereira; Satoshi Hirata (Mammal Research, 2019)

Spatial positioning of individuals in a group of feral horses: a case study using drone technology - Sota Inoue; Shinya Yamamoto; Monamie Ringhofer; Renata S. Mendonça; Carlos Pereira; Satoshi Hirata (Mammal Research, 2019)

A pathological study of the tongues of rabid dogs in the Philippines - Nozomi Shiwa; Kazunori Kimitsuki; Daria Llenaresas Manalo; Satoshi Inoue; Chun-Ho Park (Archives of Virology, 2018)

Comparison of the social systems of primates and feral horses: data from a newly established horse research site on Serra D’Arga, northern Portugal - Monamie Ringhofer; Sota Inoue; Renata S. Mendonça; Carlos Pereira; Tetsuro Matsuzawa; Satoshi Hirata; Shinya Yamamoto (Primates, 2017)

Thrombolysis with Low-Dose Tissue Plasminogen Activator 3–4.5 h After Acute Ischemic Stroke in Five Hospital Groups in Japan - Ryuta Morihara; Syoichiro Kono; Kota Sato; Nozomi Hishikawa; Yasuyuki Ohta; Toru Yamashita; Kentaro Deguchi; Yasuhiro Manabe; Yoshiki Takao; Kenichi Kashihara; Satoshi Inoue; Hideki Kiriyama; et al. (Translational Stroke Research, 2016)

Efficient expansion of mouse primary tenocytes using a novel collagen gel culture method - Akemi Shimada; Satoshi Wada; Kouji Inoue; Hisashi Ideno; Taichi Kamiunten; Koichiro Komatsu; Akira Kudo; Yoshiki Nakamura; Tetsuji Sato; Kazuhisa Nakashima; Akira Nifuji (Histochemistry and Cell Biology, 2014)

High-resolution observations of dissolved isoprene in surface seawater in the Southern Ocean during austral summer 2010–2011 - Sohiko Kameyama; Satoshi Yoshida; Hiroshi Tanimoto; Satoshi Inomata; Koji Suzuki; Hisayuki Yoshikawa-Inoue (Journal of Oceanography, 2014)

Development of microsatellite markers for Astrotrichilia asterotricha (Meliaceae), an endemic tree in Madagascar, using next-generation sequencing technology - Hiroki Sato; Christopher Adenyo; Tsuyoshi Harata; Satoshi Nanami; Akira Itoh; Yukio Takahata; Miho Inoue-Murayama (Conservation Genetics Resources, 2013)

Plasmid-mediated bioaugmentation of sequencing batch reactors for enhancement of 2,4-dichlorophenoxyacetic acid removal in wastewater using plasmid pJP4 - Hirofumi Tsutsui; Yasutaka Anami; Masami Matsuda; Kurumi Hashimoto; Daisuke Inoue; Kazunari Sei; Satoshi Soda; Michihiko Ike (Biodegradation, 2013)

Down-regulation of miR-124/-214 in cutaneous squamous cell carcinoma mediates abnormal cell proliferation via the induction of ERK - Keitaro Yamane; Masatoshi Jinnin; Tomomi Etoh; Yuki Kobayashi; Naoki Shimozono; Satoshi Fukushima; Shinichi Masuguchi; Keishi Maruo; Yuji Inoue; Tsuyoshi Ishihara; Jun Aoi; Yuichi Oike; et al. (Journal of Molecular Medicine, 2013)

Antigen capture ELISA system for henipaviruses using polyclonal antibodies obtained by DNA immunization - Yoshihiro Kaku; Akira Noguchi; Glenn A. Marsh; Jennifer A. Barr; Akiko Okutani; Kozue Hotta; Boldbaatar Bazartseren; Christopher C. Broder; Akio Yamada; Satoshi Inoue; Lin-Fa Wang (Archives of Virology, 2012)

Impacts of gene bioaugmentation with pJP4-harboring bacteria of 2,4-D-contaminated soil slurry on the indigenous microbial community - Daisuke Inoue; Yuji Yamazaki; Hirofumi Tsutsui; Kazunari Sei; Satoshi Soda; Masanori Fujita; Michihiko Ike (Biodegradation, 2012)

Climate change impacts on international seaports: knowledge, perceptions, and planning efforts among port administrators - Austin Becker; Satoshi Inoue; Martin Fischer; Ben Schwegler (Climatic Change, 2012)

Soil frost control: agricultural adaptation to climate variability in a cold region of Japan - Tomoyoshi Hirota; Kazuei Usuki; Masaki Hayashi; Manabu Nemoto; Yukiyoshi Iwata; Yosuke Yanai; Tomotsugu Yazaki; Satoshi Inoue (Mitigation and Adaptation Strategies for Global Change, 2011)

Temozolomide Delivery to Tumor Cells by a Multifunctional Nano Vehicle Based on Poly(β-L-malic acid) - Rameshwar Patil; José Portilla-Arias; Hui Ding; Satoshi Inoue; Bindu Konda; Jinwei Hu; Kolja A. Wawrowsky; Paul K. Shin; Keith L. Black; Eggehard Holler; Julia Y. Ljubimova (Pharmaceutical Research, 2010)

Evaluation of the biodegradation potential of 1,4-dioxane in river, soil and activated sludge samples - Kazunari Sei; Takashi Kakinoki; Daisuke Inoue; Satoshi Soda; Masanori Fujita; Michihiko Ike (Biodegradation, 2010)

Turnip yellow mosaic virus isolated from Chinese cabbage in Japan - Namiko Kirino; Koji Inoue; Koji Tanina; Yuya Yamazaki; Satoshi T. Ohki (Journal of General Plant Pathology, 2008)

Deoxymugineic acid increases Zn translocation in Zn-deficient rice plants - Motofumi Suzuki; Takashi Tsukamoto; Haruhiko Inoue; Satoshi Watanabe; Shinpei Matsuhashi; Michiko Takahashi; Hiromi Nakanishi; Satoshi Mori; Naoko K. Nishizawa (Plant Molecular Biology, 2008)

Identification and localisation of the rice nicotianamine aminotransferase gene OsNAAT1 expression suggests the site of phytosiderophore synthesis in rice - Haruhiko Inoue; Michiko Takahashi; Takanori Kobayashi; Motofumi Suzuki; Hiromi Nakanishi; Satoshi Mori; Naoko K. Nishizawa (Plant Molecular Biology, 2008)

The expression of iron homeostasis-related genes during rice germination - Tomoko Nozoye; Haruhiko Inoue; Michiko Takahashi; Yasuhiro Ishimaru; Hiromi Nakanishi; Satoshi Mori; Naoko K. Nishizawa (Plant Molecular Biology, 2007)

Diethylstilbestrol increases the density of prolactin cells in male mouse pituitary by inducing proliferation of prolactin cells and transdifferentiation of gonadotropic cells - Keiko Shukuwa; Shin-ichi Izumi; Yoshitaka Hishikawa; Kuniaki Ejima; Satoshi Inoue; Masami Muramatsu; Yasuyoshi Ouchi; Takashi Kitaoka; Takehiko Koji (Histochemistry and Cell Biology, 2006)

Changes in Immune Responses to Antigen Applied to Tape-Stripped Skin with CpG-Oligodeoxynucleotide in NC/Nga Mice - Joe Inoue; Satoshi Yotsumoto; Takatoshi Sakamoto; Seishi Tsuchiya; Yukihiko Aramaki (Pharmaceutical Research, 2005)

Nephrotoxicity of a novel antineoplastic platinum complex, nedaplatin: a comparative study with cisplatin in rats - Takeki Uehara; Hiroshi Watanabe; Fumio Itoh; Satoshi Inoue; Hikaru Koshida; Masuhisa Nakamura; Jyoji Yamate; Toshiyuki Maruyama (Archives of Toxicology, 2005)

Abstract of Poster Presentation - Hiroshi Uchida; Tetsuo Maruyama; Jkuko Sugiura; Takashi Kajitani; Touru Arase; Masanori Ono; Takashi Nagashima; Hirotaka Masuda; Hironori Asada; Yasunori Yoshimura; Soichiro Saito; Mila Ghosh; et al. (Human Cell, 2005)

Different effects of constitutive nitric oxide synthase and heme oxygenase on pulmonary or liver metastasis of colon cancer in mice - Takeshi Ishikawa; Norimasa Yoshida; Hiroshi Higashihara; Mamoru Inoue; Kazuhiko Uchiyama; Tomohisa Takagi; Osamu Handa; Satoshi Kokura; Yuji Naito; Takeshi Okanoue; Toshikazu Yoshikawa (Clinical & Experimental Metastasis, 2003)

Estimating the beginning day of Japanese cedar pollen release under global climate change - SATOSHI INOUE; SHIGETO KAWASHIMA; YUICHI TAKAHASHI (Global Change Biology, 2002)
This study examined the effects of snowfall on the beginning day of Cryptomeria japonica pollen release and predicted it under global climate change. We used a statistical method in order to investigate when the pollen release would start and how much sooner it would be, by using data on predicted meteorological conditions under global warming in Yamagata City, Japan. Estimation accuracy was improved by multiple regression by using the mean air temperature from January to February and snowfall depth in February. Adding snowfall depth yielded more accurate estimates of the beginning day of pollen release than using air temperature alone. It is possible that the effects of heat insulation and cooling by snow delay the flowering day. Under the predicted global climate change, we expect the beginning day of pollen release to become earlier in Yamagata City. The date would be 8 February in approximately 100 years, compared with 20 February at the earliest now. Eighty years from now the date could be earlier than any date recorded so far.

Influence of Acid Deposition on Inland Water Chemistry - A Case Study from Hyogo Prefecture, Japan - - Yukio Komai; Satoshi Umemoto; Takanobu Inoue (Water, Air, & Soil Pollution, 2001)

Ultrastructural changes in motor endplates of the lumbrical muscles of rats induced by a microsomal Ca 2+ ATPase inhibitor, 2,5-di(tert-butyl)-1,4-hydroquinone - Kunitoshi Mitsumori; Takayoshi Imazawa; Hiroshi Onodera; Michihito Takahashi; Satoshi Kitajima; Tohru Inoue; Yuji Kurokawa (Archives of Toxicology, 1997)